More than the sum of their parts expanding the scope of particle accelerators. (Research'eu results magazine)
With the performance frontiers of existing infrastructure streched, the EU-funded EUCARD-2 project was set up to enhance particle accelerators for basic and applied science. The project succeeded in rendering their design more compact and more sustainable than traditional options.